Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Course Review Horay (CRH) Terhadap Keaktifan Belajar dan Hasil Belajar Ekonomi - Aisyah Aisyah (Soedirman Economics Education Journal, 2019)
This research is experimental research on students class XI of MIPA in SMA Negeri 3 Purwokerto. This research takes the title of "The Influence of the Application of the Cooperative Learning Model Type Course Review Horay (CRH) Against the Liveliness of learning and the Results of the Economic Study (study on the Grade XI MIPA in SMA Negeri 3 Purwokerto)". The purpose of this research is to know the difference in learning outcomes and learning activity between the learning model Course Review Horay (CRH) with conventional learning model, to know the influence of learning model Course Review Horay (CRH) against the learning outcomes and learning activity, as well as to know the influence of the liveliness of the learning results of learning. The population of this research is the grade XI MIPA in SMA Negeri 3 Purwokerto. The number of samples taken in this study is 72 i.e. 2 Class XI of MIPA which each class amounted to 36 students. Purposive Sampling Method used in the determination of the sample. Based on the results of the research and the anallisis data indicate that (1) there is a significant difference between the model of learning learning activeness cooperative Course Review Horay (CRH) and conventional learning model on economics. (2) there are significant differences between the learning outcomes learning model cooperative Course Review Horay (CRH) and conventional learning model on economi. (3) there is a positive influence learning model cooperative Course Review Horay (CRH) against the liveliness of the study on economic. (4) there is a positive influence learning model cooperative Course Review Horay (CRH) against the results of the study on economic. (5) there is no positive influence between the liveliness of student learning against the results of the study on economic. Penelitian ini adalah penelitian eksperimen pada siswa kelas XI MIPA di SMA Negeri 3 Purwokerto. Penelitian ini mengambil judul “Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Course Review Horay (CRH) terhadap Keaktifan Belajar dan Hasil Belajar Ekonomi (Studi pada Siswa Kelas XI MIPA di SMA Negeri 3 Purwokerto)”. Tujuan dari penelitian ini adalah untuk mengetahui perbedaan keaktifan belajar dan hasil belajar antara model pembelajaran Course Review Horay (CRH) dengan model pembelajaran konvensional, untuk mengetahui pengaruh model pembelajaran Course Review Horay (CRH) terhadap keaktifan belajar dan hasil belajar, serta untuk mengetahui pengaruh keaktifan belajar terhadap hasil belajar. Populasi penelitian ini adalah siswa kelas XI MIPA di SMA Negeri 3 Purwokerto. Jumlah sample yang diambil dalam penelitian ini adalah 72 yaitu 2 kelas XI MIPA yang masing-masing kelas berjumlah 36 siswa. Purposive Sampling Method digunakan dalam penentuan sample. Berdasarkan hasil penelitian dan anallisis data menunjukkan bahwa (1) Terdapat perbedaan signifikan keaktifan belajar antara model pembelajaran kooperatif Course Review Horay (CRH) dengan model pembelajaran konvensional pada mata pelajaran ekonomi. (2) Terdapat perbedaan signifikan hasil belajar antara model pembelajaran kooperatif Course Review Horay (CRH) dengan model pembelajaran konvensional pada mata pelajaran ekonomi. (3) Terdapat pengaruh positif model pembelajaran kooperatif Course Review Horay (CRH) terhadap keaktifan belajar pada mata pelajaran ekonomi. (4) Terdapat pengaruh positif model pembelajaran kooperatif Course Review Horay (CRH) terhadap hasil belajar pada mata pelajaran ekonomi. (5) Tidak terdapat pengaruh positif antara keaktifan belajar siswa terhadap hasil belajar pada mata pelajaran ekonomi.